Analysis of Coprocessor-based Acceleration for Hardware-based Semaphore Concurrency Control - Walichiewicz, Michal; Milik, Adam (International Journal of Electronics and Telecommunications, 2026)
Coprocessors are widely integrated into modern microprocessors, particularly in safety-critical systems. They handle interrupts and accelerate computationally intensive operations, such as cryptographic and floating-point calculations; furthermore, they enable separation between system components. This article adopts a structured approach to provide a formal description of coprocessors and their role within modern microprocessor architectures. In addition, a concurrency control system based on Inter-Processor Interrupts (IPIs) is presented and compared with a polling-based synchronization approach using hardware-based semaphores. Finally, this study evaluates whether coprocessors can be utilized to accelerate multi-core synchronization by executing computations in parallel with synchronization.